The abduction of Libya’s prime minister : militias run rampant - Ahmed Salah Hashim (2014)
On 10 October, 2013, Libyan Prime Minister Ali Zeidan was briefly abducted by one of Libya’s numerous militia groups but was released unharmed hours later. His abduction may have more to do with the peculiar dynamics of post-revolutionary politics in Libya.